Radiographic comparison of atelocollagen versus deproteinized bovine bone minerals covered with a collagen membrane in alveolar ridge preservation: a retrospective study - Sha You; Fan Yu; Qihang Fan; Ting Xia; Liang Liang; Qi Yan; Hao Zeng; Bin Shi (BMC Oral Health, 2023)
Abstract Background Atelocollagen (AC) is a low-immunogenic collagen derivative with longer degradation time, which can be a suitable material for alveolar ridge preservation (ARP). However, there are few human studies on AC using for ARP. This research aims to radiographically evaluate the efficacy of AC in comparison to deproteinized bovine bone minerals covered with a collagen membrane (DBBM/CM) in ARP. Methods Medical records in the Implantology Department of the Hospital of Stomatology of Wuhan University were screened for patients who received flapless ARP using either AC or DBBM/CM. A total of 58 patients were included in this retrospective study. 28 patients were treated with AC, while 30 patients were used DBBM/CM. Cone-beam computed tomography (CBCT) scans were taken before extraction and after 6 months of healing. To assess the dimensional change of the extraction sockets, the scanning data were output and transferred to the digital software to measure horizontal bone width change, vertical bone height change and bone volume change in region of interest. To evaluate the bone quality of healed sockets, the bone density of virtual implants was evaluated. Results The horizontal bone width changes at all five different levels showed no significant difference between the two groups. The largest horizontal bone width decrement in both groups occurred at the crest of ridge, which decreased 3.71 ± 1.67 mm in AC group and 3.53 ± 1.51 mm in DBBM/CM group (p = 0.68). At the central buccal aspect, the ridge height reduced 0.10 ± 1.30 mm in AC group, while increased 0.77 ± 2.43 mm in DBBM/CM group (p = 0.10). The vertical bone height differences between two groups showed no statistical significance. The percentages of volume absorption in AC group and DBBM/CM group were 12.37%±6.09% and 14.54%±11.21%, respectively. No significant difference in volume absorption was found (p = 0.36). The average bone density around virtual implants in AC group (649.41 ± 184.71 HU) was significantly lower than that in DBBM/CM group (985.23 ± 207.85 HU) (p < 0.001). Conclusions ARP with AC had a similar effect on limiting the dimensional alteration of alveolar ridge, when radiographically compared with DBBM/CM.